COMPLICATED SIGMOID DIVERTICULOSIS, PERFORATIVE DIVERTICULITIS - Подолужный, Валерий Иванович; Павленко, Владимир Вячеславович; Старцев, Андрей Борисович; Каменева, Евгения Александровна; Пельц, Владислав Александрович (Medicine in Kuzbass, 2025)
The aim of the study – to assess the frequency and structure of the incidence of diverticulosis and perforated diverticulitis of the sigmoid colon in the dynamics of twenty years of treatment of this pathology in Kemerovo. Materials and methods. Annual reports and case histories of patients undergoing treatment for two decades were analyzed (2004-2013 and 2014-2023) in the surgical department N 1 of the Kuzbass Clinical Emergency Hospital named after. M.A. Podgorbunsky. Incidence was assessed by the number of patients treated per 100000 city residents. Results. Over the past decade, the number of patients treated with complications of sigmoid diverticulosis has increased from 40.4 to 78.7 per 100000. The number of patients operated on with perforated diverticulitis has increased from 6.6 to 12.7 per 100000 of the city population. Among those operated on, women predominated (57.1%). The average age of patients with perforated diverticulitis has decreased in the last decade from 78.4 to 66.6 years. Over two decades, 74.7% underwent intestinal resection with colostomy (77 people), 20.4% (21 people) with microperforation and the formation of infiltrates underwent laparoscopy with drainage of the abdominal cavity, and in 4.85% (5 people) drainage of abscesses under ultrasound control. Postoperative mortality over the past 10 years has decreased from 9 to 8.5%. Conclusion. There is an increase in the number of patients with diverticulosis and perforated diverticulitis of the sigmoid colon, there is a decrease in the average age of patients, women predominate. Postoperative mortality over the past two decades is within 8.5-9%.